2020
DOI: 10.1186/s43019-020-0029-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic kidney disease on outcomes of total joint arthroplasty: a meta-analysis

Abstract: Background: This meta-analysis was conducted to evaluate the differences in preoperative comorbidities, postoperative mortality, the rate of periprosthetic joint infection (PJI), and revision rate after total joint arthroplasty (TJA) between patients with chronic kidney disease (CKD)(CKD group) and patients with normal kidney function (non-CKD group). Methods: We searched MEDLINE, EMBASE, and the Cochrane Library for studies assessing the effect of CKD on TJA outcome. This meta-analysis included studies that (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…The effect of renal disease on mortality in patients who underwent TKA has been investigated in several studies 20 , 23 , 28 33 . In the meta-analysis of mortality, the hazard ratio of mortality after TKA was significantly higher in patients with chronic kidney disease (HR = 1.45; 95% CI = 1.02–2.05, P = 0.04) 31 . Hunt et al reported that renal disease increased the risk of 45-day mortality after TKA in a study involving a large national registry (HR = 2.18; 95% CI = 1.76 to 2.69, P < 0.0005) 23 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The effect of renal disease on mortality in patients who underwent TKA has been investigated in several studies 20 , 23 , 28 33 . In the meta-analysis of mortality, the hazard ratio of mortality after TKA was significantly higher in patients with chronic kidney disease (HR = 1.45; 95% CI = 1.02–2.05, P = 0.04) 31 . Hunt et al reported that renal disease increased the risk of 45-day mortality after TKA in a study involving a large national registry (HR = 2.18; 95% CI = 1.76 to 2.69, P < 0.0005) 23 .…”
Section: Discussionmentioning
confidence: 97%
“…The decrease in renal perfusion due to perioperative blood loss is expected to adversely affect the progression of renal disease and could increase the risk of mortality. Renal disease could also affect the risk of complications such as peri-prosthetic joint infection and rate of arthroplasty revision surgery 31 , 33 . Therefore, careful preoperative risk stratification is important in patients with renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal interim period for performing a THA after septic arthritis is debatable, and no consensus has been reached [54]. A recent multicentre study employing a receiver operating characteristic (ROC) analysis indicated that [45] Serum creatinine >1.5 mg/dL; Creatinine clearance rate < 100 mL/min Anaemia (Hb < 9 g/dL) [46] Smoking Recent history of intra-articular injection [47] Inflammatory arthritis [48], Previous septic arthropathy [49] Systemic infectious process [50] 5.9 months after the initial treatment might represent a suitable timepoint. However, when the population was dichotomised by this threshold, the authors reported no difference with respect to the PJI rate [55].…”
Section: Preventing Prosthetic Joint Infectionmentioning
confidence: 99%
“…Several risk factors have been associated with an increased risk of PJI, including obesity, liver disease, diabetes, and renal disease. 6 , 7 The relationship between renal disease and PJI is not fully understood, but it has been hypothesized that electrolyte imbalances 8 and the blunting of the immune system caused by uremia and systemic inflammation are possible mechanisms. 9 - 11 Moreover, as the condition progresses to renal failure, the two treatment options available, dialysis and renal transplant (RT), both further increase PJI risk.…”
mentioning
confidence: 99%
“…This is particularly problematic because both treatments have been associated with amyloid deposition, osteonecrosis, renal osteodystrophy, and osteoarthritis, all of which increase the need for TJA. 6,[12][13][14][15] Thus, a deeper understanding of the interplay between ESRD, RT, and TJA outcomes is necessary to better care for patients who simultaneously have a greater need for TJA and a greater risk for adverse complications after TJA.…”
mentioning
confidence: 99%